Detection of latent DNA on tape-lifts using fluorescent in situ detection. Issue 4 (4th July 2019) - Haines, Alicia M.; Linacre, Adrian
ABSTRACT : Tape-lifts can be used for the removal of a range of evidence types without damaging the substrate. In addition to loosely adhering material such as hairs and fibres, tape-lifts can be used to remove latent cellular material on clothing that had originated from the wearer's body or mouth. Common forensic practice is to examine the entire tape-lift in a non-targeted approach. An innovative field of research uses DNA binding dyes for the detection of latent DNA. This research describes the use of these DNA binding dyes as a DNA-targeted screening tool for tape-lifts. The individual cells can be visualized allowing the relevant area of the tape to be removed for subsequent DNA typing. Full single source DNA profiles were generated that matched the expected control sample after staining tape-lifts with two different dyes. Direct amplification was undertaken from tape-lifts of samples where biological material had been deposited over 12 months previously, from which a DNA profile matching the donor was obtained. The process outlines an effective means to visualize the presence of cellular material from which STR profiles can be generated allowing a targeted approach to be performed.